Upwellings, canyons and whales: An important winter habitat for balaenopterid whales off Mauritania, northwest Africa - Baines, Mick E.; Reichelt, Maren (J. Cetacean Res. Manage., 2023)
The aim of this study was to identify critical habitats for baleen whales in the Mauritanian upwelling zone using data collected from a platform of opportunity: a 60 day geophysical survey approximately 100km southwest of Cap Blanc, Mauritania in winter (2012/13). The bathymetry of the 5,500km2 study area was complex, including parts of the Cap Timiris Canyon system. Large whales, including sei and blue whales, accounted for 70% of the 238 cetacean sightings. Species identification was often problematic, especially in the case of balaenopterid whales, so data for all whales of this genus were pooled for the estimation of abundance and distribution. Spatial modelling was applied to estimate abundance and to plot a predicted density map of balaenopterid whales. Depth and the chlorophyll-a concentration when at its peak (in the previous September) were significant predictors of whale density. Point abundance in the study area was estimated at 272 whales (95% CI 265–279) and density was highest in the depth range 500–2,250m near to the canyon system (6.18 whales/100km2 , 95% CI 6.03–6.51). Steep seabed topography created by canyons running off the shelf edge, together with the strong upwelling system, probably create optimal habitats for the euphausiid prey of sei and blue whales. Sei whales were observed skim-feeding at dawn or dusk on seven occasions; in one sighting an aggregation of 18 skim-feeding sei whales were observed. The high density of these baleen whale species in such a highly productive area and direct observation of feeding behaviour in sei whales, provides evidence of feeding during the winter breeding season, when they have previously been presumed to feed less. This study demonstrates the potential value of collecting further data on seismic survey vessels and would improve understanding of cetacean ecology in remote and under-explored regions.